Evaluating the Impact of NEP 2020: Undergraduates' Understanding of Yoga and Physical Education in Betul District - Deeepak Kumar Hatia; Vikash Saxena (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Study purpose: This study, therefore, investigates the extent to which undergraduate students in Betul district are aware of the provisions and objectives of NEP 2020 pertaining to yoga and physical education, and evaluates their existing knowledge levels in these areas (Soni, 02024). Method: Necessary instruction required before answering the questionnaire was explained to the subject. Gathered the topic and described the study's objectives. 20 min. time was given to answer the question. During filling out the questionnaire to explain those questions, it is not understood by the subject. Regularly check the subject that no question was left unanswered. Aware the subjects about NEP .5 point LIKERT scale questionnaire were employed to answer .Descriptive statistics was used to answer the question. In conclusion, the outcomes of the discussions show that modifications are needed in order to successfully implement the practical class for the active learning strategy to construct the practical class in those colleges. Discussion: The outcomes of the discussions show that adjustments are needed in order to implement the practical class for the active learning strategy to construct the practical class in those universities. Teachers should be encouraged to become more knowledgeable about and skilled at using practical active learning techniques in the classroom. Workshops, seminaries, and inter-staff conversations in the form of seminar training that promotes idea sharing to improve teachers' understanding of application active learning can do this. Conclusion: Instructors should be urged to increase their knowledge and proficiency in using real-world active learning strategies in the classroom. This can be accomplished through workshops, seminaries, and inter-staff discussions in the form of seminar training that encourages idea exchange to enhance teachers' comprehension of application active learning. Key Word: Education, Descriptive, National Education Policy, Yoga